2003
DOI: 10.2320/matertrans.44.1802
|View full text |Cite
|
Sign up to set email alerts
|

Strain Enhanced Growth of Precipitates during Creep of T91

Abstract: The previous work showed that the precipitate coarsening of T91 (Modified 9Cr-1Mo steel) was described by an empirical relationship depending on applied stress. However, there is another possibility that the stress dependent coarsening is merely apparent and strain dependent actually. In the present paper, an attempt was made to re-analyze the previous data based on a model in which the effective diffusivity of solute is strain dependent. The result of analysis suggests strongly that the dislocation dragging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Carbide coarsening is accelerated under applied load, which is consistent with Hättestrand and Andrén (2001), Nakajima et al (2003), Cerri et al (1998), Eggeler (1989) and Engberg et al (1984). For long term ageing (more than 10,000 h), stress no longer influences the coarsening kinetics and the final average size of the carbides is about 250 nm both with and without applied stress.…”
Section: Ageing and Softening Effectssupporting
confidence: 87%
“…Carbide coarsening is accelerated under applied load, which is consistent with Hättestrand and Andrén (2001), Nakajima et al (2003), Cerri et al (1998), Eggeler (1989) and Engberg et al (1984). For long term ageing (more than 10,000 h), stress no longer influences the coarsening kinetics and the final average size of the carbides is about 250 nm both with and without applied stress.…”
Section: Ageing and Softening Effectssupporting
confidence: 87%
“…[31][32][33][34] Both a large carbide size and a low carbon content promote rapid softening of martensite during a high temperature tempering treatment. 35) The hardness profile of Fig.…”
Section: Effects Of the Pwhtmentioning
confidence: 99%
“…Effects of the PWHT Several studies of the base metal have shown that the microstructural stability of 9Cr1Mo-NbV steels, especially under high temperature ageing and creep conditions, strongly depends on the pinning of dislocations and grain boundaries by a fine distribution of carbides. [31][32][33][34] Both a large carbide size and a low carbon content promote rapid softening of martensite during a high temperature tempering treatment. …”
mentioning
confidence: 99%
“…The magnitude of L value is dependent of dislocation velocity, solute concentration in matrix, temperature and the size misfit of solutes, 25,26) however, it remains constant as long as the dislocation velocity remains unchanged. Using D l for grip parts and D 0 for gauge parts, the enhanced coarsening of precipitates in Al-Cu alloy, 14) Mod.9Cr-1Mo steel 22,23) and magnesium alloy of AZ80 24) can be explained reasonably by the scavenging effect. The detail will be published elsewhere.…”
Section: Scavenging Effectmentioning
confidence: 99%
“…One of the probable mechanisms is the scavenging effect of dislocation. [21][22][23] As mentioned already, an aluminum atom has a noticeable size misfit to the solvent atom of AZ80 alloy, so that a solute atmosphere is formed around a dislocation due to an elastic interaction. 24) Since the drift velocity of solutes given by the Einstein's equation is higher than the dislocation velocity at least within the solute atmosphere, the solute atmosphere lag behind dislocations.…”
Section: Scavenging Effectmentioning
confidence: 99%